'Look beyond skin': psychogenic excoriation - a series of five cases - Balakrishnan Nirmal; Shrutakirthi D Shenoi; Shweta Rai; Kongasseri Sreejayan; Soman Savitha (Wolters Kluwer Medknow Publications, 2013)
Psychogenic excoriation is a condition where the patient picks the skin repetitively to produce excoriations. Treating this clinical entity is challenging as these patients often have an associated psychological abnormality. The five cases in this case series include two children and three adults. They presented with skin lesions ranging from excoriations and ulcers to scars and pigmentation. Detailed evaluation was done by clinical psychologist. Two cases had anxiety traits, one had alcohol dependence, one had difficult temperament and one had depressive symptoms. Habit reversal was introduced. Psychiatry referral was given for three cases and started on selective serotonin reuptake inhibitors. On follow-up, the urge to scratch reduced substantially and skin lesions were also improving. It is important to identify the underlying psychological disorder accounting for skin picking behavior. Incorporating psychotherapeutic techniques into clinical practice will improve the quality of life of many of these patients.